Menstrual Dysfunction and Athletic Performance in a Transgender Runner: A Case Study. Issue 11 (November 2021) - Holtzman, Bryan; H. M. O'Brien, Kimberly; Reece, Laura M.; Ackerman, Kathryn E.
Abstract: A 16.5-year-old, distance runner, female gender-assigned at birth, who identifies as male, presented with menstrual dysfunction and impaired athletic performance. The cause of the menstrual dysfunction and decreased athletic performance was identified as inadequate energy availability, largely motivated by a desired avoidance of menstruation and further development of secondary sex characteristics. The patient achieved significant weight gain (4.75 kg) in the year after presentation and resumed normal menses. When evaluating and treating transgender athletes for menstrual dysfunction and inadequate energy availability, psychological motivators related to the complex interplay between gender identity, disordered eating, and athletic performance must be addressed.